Penggunaan Media Video Untuk Meningkatkan Hasil Belajar Pada Pembelajaran IPA Siswa Kelas V SD Kristen 3 Bangunan Wuwuk - Tempay, Tiara Junistri Katrin; Rorimpandey, Widdy H. F.; Liando, Maxie A. J. (Peneliti.net, 2024)
This research is classroom action research (PTK) which consists of four stages, namely planning, action, observation and reflection. This research aims to improve student learning outcomes in science lessons in class V of SD Kristen 3 Gedung Wuwuk. This research was carried out in two cycles. The subjects in this research were class V students at SD Kristen 3 Gedung Wuwuk, totaling 11 students consisting of 8 boys and 3 girls. Data about learning activities in class was obtained from teacher observations in managing learning, and tests on student learning outcomes. The data obtained is processed and uses analysis techniques with predetermined learning completeness criteria. Data analysis to determine student learning outcomes, whether they have met the criteria for learning completeness or not. The results of the research showed that the results obtained from the use of video media in science learning were 62.2% in the first cycle and 86.8% in the second cycle. Based on the results of analysis of achievement data in cycles I and II, it turned out that there was an increase of 24.6%, so it can be concluded that the use of video media can improve student learning outcomes in science learning in class V at Christian Elementary School 3 Gedung Wuwuk.